Reinterpreting Khadījah's domestic and social agency: Insights from Fatima Mernissi's gender perspective - Fitria Wahud; Widya Ningsih; Rif’atul Khoiriah Malik; Faizah Binti Awad; Eldar Kafarov (An-Nisa’ Journal of Gender Studies, 2026)
The role of Muslim women is often reduced to domesticity, while their social contributions remain marginalized. The figure of Khadījah is therefore important to examine to challenge patriarchal bias and affirm gender agency in early Islamic history from a critical contemporary perspective. This study aims to analyze Khadījah’s role as a Muslim woman who embodied domestic, social, and gender agency in early Islam through the perspective of Fatima Mernissi. This study employs descriptive qualitative library research design, analyzed using Braun and Clarke’s thematic analysis and Mernissi’s gender perspective. The data were drawn from historical sources, biographies, ḥadīth, journal articles, and source triangulation to ensure critical data validity. The findings reveal three main points. First, Khadījah’s domestic role was demonstrated through emotional, moral, material, and spiritual support that strengthened the Prophet’s family and sustained the early prophetic mission. Second, her social role was reflected in solidarity, sacrifice, and public leadership during the Quraysh boycott, which strengthened the resilience of the early Muslim community. Third, from Mernissi’s perspective, Khadījah represents gender agency through patriarchal critique, egalitarian relations, and public participation in early Islamic social transformation. The study concludes that Khadījah represents multidimensional Muslim women’s agency through domestic support, social leadership, and patriarchal critique. This study recommends strengthening historical-critical readings of Khadījah as a model for Muslim women’s empowerment through Islamic gender education, egalitarian family partnership, and broader women’s social participation.